Fractionally Nyquist Sample Spaced ARMA Blind Equalizer for Direct Signal Recovery in Passive Bistatic Radar. Issue 3 (1st May 2017) - Wang, Feng; Shen, Wei; Jiang, Defu; Wei, Shuang
Abstract : This paper proposes a modified signal processing structure based on the fractionally Nyquist sample spaced structure for passive bistatic radar. To recover the direct signal from the multipath clutter, an equalizer of the Auto regressive moving average (ARMA) type is proposed based on the fractionally Nyquist sample spaced constant modulus algorithm. Compared with the conventional Nyquist sample spaced equalizer, the equalizer of the fractionally Nyquist sample spaced ARMA structure is more effective in dealing with deep fading multipath channels with zeros near the unit circle. Computer simulations and real data tests indicate that the proposed approach outperforms the conventional processing structure in terms of both clutter residual and mean square error.